Aural myiasis caused by Lucilia sericata in an asymptomatic patient with dementia - Yasunori Maeda; Yusuke Kimura; Junnosuke Abe; Takeomi Ikematsu; Yasuyuki Nomura; Takeshi Oshima (IDCases)
This study amied to elucidate the case of an older patient suffering from aural myiasis caused by Lucilia sericata. An 81-year-old female patient with a history of middle ear surgery and dementia presented with bleeding in her right ear and visible worms. Upon initial examination, a larva was found crawling on the right auricle. Further examination revealed numerous larvae, purulent otorrhea, and active bleeding in the external auditory canal and mastoid cavity. All larvae were successfully removed with ear irrigation. The patient was diagnosed with otitis media and treated with antibiotic ear drops, resulting in significant clinical improvement. The larvae were later identified morphologically as Lucilia sericata, a species of Calliphoridae. This case highlights the potential for aural myiasis in elderly patients with dementia and otitis media, who may be at increased risk for the condition.